Trend Research of Project-Based Learning in The Database Scopus 1964-2023 - Zahra, Afifah Nur; Maksum, Muh. Nur Rochim; Chusniatun, C; Apriantoro, Muhamad Subhi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research intends to track the progress and focus of project-based learning research in Scopus publications. Researchers focus on analyzing Scopus-indexed publications on project-based learning from 1964 to 2023 using bibliometric analysis techniques. Data was analysed using Excel, R/R-Studio. VOSviewer provides a visual analysis of keywords and document citations co-occurring. The author found research data of 1,803 published documents according to the function, subject, and criteria specified. This research demonstrates an annual growth rate of 8.04% for project-based learning research and the highest number of publications in 2022. The United States had the most research papers, while National Taiwan Normal University had the most document affiliates. Barak, M. and Yang, S.C. became the most productive writers on project-based learning themed. Researchers were limited to using Scopus data for bibliometric analysis. The study solely focused on one database without considering other national or international databases. The research presents a brief literature review on learning methods for educators, with recommendations for future research in the field of education.